F47. EXPERIMENTALLY INDUCING PARANOIA IN A HEALTHY POPULATION. (9th April 2019) - Klein, Hans; Bass, Emily; Pinkham, Amy
Abstract: Background: Attempts to understand paranoia in healthy populations have noted correlations between levels of subclinical paranoia and psychological traits (e.g. anxiety, Tone et al, 2001; or depression, Combs & Penn, 2004), social perception (Combs et al., 2013, Klein, Kelvesen, & Pinkham, 2018), and functioning (Rossler et al., 2007). However, these cross-sectional observations preclude a causal understanding of the effects of paranoia. The current study seeks to validate an experimental procedure to induce paranoia in a healthy population to determine if paranoia can be acutely exacerbated and the effects this may have on anxiety. Methods: As part of a larger neuroimaging study, undergraduate participants were recruited based on varied levels of subclinical paranoia. Sixty-four participants were randomly assigned to either a control or paranoia induction condition resulting in 32 participants per condition. The paranoia induction procedure included receiving false negative feedback, completing a social exclusion task, and overhearing ambiguous comments between two experimenters that can be inferred to be commentary about the participant. State levels of anxiety (State Trait Anxiety Inventory; STAI-S) and social paranoia (State Social Paranoia Scale - persecution subscale, SPSS) were recorded both before and after the induction procedure, and change scores were assessed to validate efficacy of the procedure. Results: Independent Samples t Tests were used to assess mean change scores in reported anxiety and paranoia. The induction procedure significantly increased anxiety (M = 2.78, SD = 6.41) compared to the control condition (M = -1.13, SD = 7.51), t(61) = -2.226, p = 0.030, d = 0.560, but failed to increase persecutory ideation (M = -0.47, SD = 2.40) compared to the control condition (M = -0.50, SD = 2.26), t(62) = -0.054, p = .957, d = 0.013. Discussion: Although our induction procedure may be limited in its ability to induce persecutory ideation as measured by the SPSS in a subclinical population, the results of this study are promising in the utility of this experimental procedure in affecting symptoms associated with paranoia. These results indicate that our induction procedure is effective in producing medium effects on state level anxiety, which is intrinsically linked and believed to impact paranoid thinking (Freeman & Garety, 2014). Future work will look at concurrent neuroimaging data to determine if the induction procedure impacted neural regions associated with paranoid ideation.